Behind the mask. Journey through an epidemic: some observations of contrasting public health responses to SARS. Issue 11 (4th November 2003) - Syed, Q; Sopwith, W; Regan, M; Bellis, M A
Abstract : SARS has been called the first global epidemic of the 21st century and has been the cause of a massive and varied public health response in many countries of the world. This report describes observations made by two authors on a journey from Manchester in the United Kingdom to Chiang Mai in Thailand during the peak of global transmission. The public response to SARS, particularly characterised by the wearing of face masks, seemed to outstrip official guidance. Though of uncertain protective benefit, the wearing of masks may have contributed to the awareness of the collective and personal responsibility in combating infectious disease. Active and empowered involvement of the general public in implementing and cooperating with public health control measures supported by national and international authorities has clearly helped to bring SARS under control. The public health significance of such potent symbols as the face mask may be considered in strategies to tackle other emerging infections.